The Image of the Self-Sacrificing Doctor: Medicine, Taxes and Unemployment in 1930s Turkey - (:unkn) unknown (OXFORD UNIV PRESS, 2015)
In 1930s Turkey, doctors frequently emphasized self-sacrifice in their public speeches through radio, talks given at various medical conventions and university lectures. This article aims to problematise this discourse through the way the doctors utilised it pragmatically to resolve certain issues that were important for their community. Two controversies will form the focus of the paper: the first concerns the employment problem of new graduates of the Faculty of Medicine. The second is the income tax controversy that took place between the doctors and government in the first half of the 1930s, during the preparations of a new tax law. In the final part of this article, I will argue that these two controversies are linked to the question of advancement of medical knowledge.
Keywords: medicine; self-sacrificing doctors; income tax; employment; Turkey; HEALTH